Tinjauan Pelaksanaan Standar Pelayanan Minimal pada Penderita Diabetes Melitus di Puskesmas Oesapa Kota Kupang Tahun 2024 - Cesilia Eleonora Molo; Serlie K.A. Littik; Rina Waty Sirait (Yayasan Literasi Sains Indonesia, 2025)
Diabetes Mellitus is a non-communicable disease that causes high morbidity and mortality, thus requiring proper and serious handling and treatment efforts. Data from the Kupang City Health Office shows that the Oesapa Community Health Center is the community health center with the highest cases of DM in Kupang City with a low achievement of 65.4% of the Oesapa Community Health Center's target of 100%. This study aims to determine the implementation of Minimum Service Standards (SPM) for diabetes mellitus patients at the Oesapa Community Health Center in Kupang City in 2024. This type of research is a qualitative descriptive study with 6 informants using a purposive technique. The results of the study indicate that input elements in the aspect of human resource availability have met the standards, sufficient funds, BMHP and medicines are available and examination tools such as glucometer tests are available. The service method provided is in accordance with the SOP. The market or target is in accordance with service standards, monitoring and evaluation are running well. The implementation of SPM at Oesapa Health Center has not reached 100% due to uneven training, unavailability of insulin, inconsistency of patients in conducting routine check-ups at Oesapa Health Center and late reporting from health posts due to low awareness of officers and busy daily services so that they do not input data on time. Therefore, the researcher suggests that the health center improve training for health workers, increase patient awareness through education, and establish a routine reporting schedule.